Cognitive Functions Buffer Age Differences in Technology Ownership - Kamin, Stefan; Lang, Frieder (Gerontology, 2016)
Background: Technology plays a major role in enhancing quality of life and everyday competence in old age. Mechanic and pragmatic cognitive functions are known to serve as resources when using technology in everyday life. Not much is known about the differential role of mechanic and pragmatic cognitive functions when moderating reduced technology ownership in old age. Objective: In this research, we explored whether perceptual speed or verbal fluency is more important for buffering age differences in technology ownership. We investigate possible moderation effects of cognitive functions relative to demographic characteristics, socioeconomic status, and household composition variables. Methods: We report findings based on a nationally representative German sample of 3,357 younger and older adults between 18 and 94 years of age (mean = 51.2, SD = 17.3). Interaction and relative importance analyses were conducted to examine the relative importance of perceptual speed and verbal fluency for the moderation of age differences in technology ownership across adulthood. Results: Findings suggest that perceptual speed (B = 0.0008, t = 6.23, p < 0.001) and verbal fluency (B = 0.0003, t = 2.70, p < 0.01) buffered age differences in technology ownership. The moderating role of perceptual speed remained robust (B = 0.0007, t = 5.48, p < 0.001) when including interactions of age with demographic, socioeconomic, and household composition variables; however, the interaction between age and verbal fluency was no longer significant (B = 0.0002, t = 1.82, p = 0.069). Relative importance analysis indicates that perceptual speed was the most important moderator of age differences (DW = 0.0121), whereas verbal fluency was less important for moderating the relation between age and technology ownership (DW = 0.0039). Conclusions: Mechanic and pragmatic cognitive functions may serve differently as moderators of the relation between age and technology ownership. Our findings suggest that perceptual speed was more important for buffering age differences in technology ownership than verbal fluency. Such findings underscore the relevance of information processing for the ownership of technological devices in late life. (C) 2015 S. Karger AG, Basel
Keywords: Technology use; Cognition; Interactions; Dominance analysis; Aging and technology; Gerontechnology